Correction to: Recent advances in surface guided radiation therapy - Freislederer, Philipp; Kügele, M.; Öllers, M.; Swinnen, A.; Sauer, T.-O.; Bert, C.; Giantsoudi, D.; Corradini, S.; Batista, Vania (Radiation oncology, 2020)
An amendment to this paper has been published and can be accessed via the original article.